A bibliometric analysis on trends and characters of carbon emissions from transport sector. (March 2018) - Tian, Xu; Geng, Yong; Zhong, Shaozhuo; Wilson, Jeffrey; Gao, Cuixia; Chen, Wei; Yu, Zhongjue; Hao, Han
Highlights: The transport sector has made substantial contribution to global greenhouse gas emissions. We conducted a Bibexcel and complex network analysis for analyzing transport sector's carbon emissions. Critical topic areas of future research on transport sector's carbon emissions have been identified. Abstract: Transport sector's substantial contribution to global greenhouse gas emissions has made it a growing area of study and concern. In order to identify trends and characteristics of carbon emissions research in the transportation sector we conducted a Bibexcel and complex network analysis for the period 1997–2016. In addition, we identify critical themes and contributions of research articles using h-index, PageRank and cluster analysis. We report contribution of countries, authors, institutions and journals, as well as performance of citations and keywords. Co-citing situations between different countries, authors, and institutions are also analyzed using network analysis. Between 1997 and 2016 we found a rise in publications on carbon emissions in the transportation sector and increased cooperation between countries, authors, and institutions. Authors from the USA, China and United Kingdom published the most articles and articles with the highest academic influence. Tsinghua University from China is the leading institution in carbon emissions research in the transportation sector. The most widely published author and cited author is Dr. He. We conclude our analysis by analyzing keywords and trends to suggest critical topic areas of future research. The systematic approach undertaken in this study can be extended and applied to other research topics and fields.